Pengaruh Rekrutmen, Pelatihan dan Motivasi terhadap Prestasi Kerja Karyawan pada PT. JNE Express Cabang Pusat Denpasar - Sekar Diari, Dewa Ayu; Ngurah Gede Sadiartha, Anak Agung; Sunny, Milla Permata (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
This research was conducted with the aim of knowing the influence of recruitment, training, motivation on employee work performance at PT. JNE Denpasar branch. In this study, the research population refers to all 118 JNE Express Denpasar branch employees with a sample size of 118 respondents determined using the saturated sample method. The data analysis techniques used in this research are validity, reliability, classical assumptions, multiple linear regression, coefficient of determination, t test and F test. Based on the research results, it can be seen that: (1) Recruitment has a positive and significant effect on employee work performance. (2) Job training has a positive and significant effect on employee work performance. (3) Motivation has a positive and significant effect on employee work performance. (4) Recruitment, training and motivation have a positive and significant effect on employee work performance. Looking at the research results, in the future PT. JNE Express Denpasar central branch is advised to be able to place employee positions according to routes that are understood. This is done to make it easier for employees to send packages because they already know the route and can enable employees to work effectively so that consumer packages can arrive on time